Studies of iron exposed to heavy ion implantation using positron annihilation spectroscopy. (May 2016) - Horodek, P.; Dryzek, J.; Skuratov, V.A.
Abstract: Variable energy positron beam and positron lifetime spectroscopy were used to study pure iron exposed to irradiation with 167 MeV Xe 26+ heavy ions with different doses of 10 12, 10 13, 5×10 13, 10 14 ions/cm 2 . The positron lifetime spectroscopy revealed the presence of large cluster of about 15–27 vacancies and dislocations. The dislocations are distributed at the depth of about 18 μm i.e. almost twice deeper than the ion implantation range from the surface exposed to the heavy ions implantation. Possible explanation is the long-range effect attributed to the ion implantation into materials. Highlights: Clusters of about 15–27 vacancies and dislocations are registered. Impact of dose on the vacancy clusters size and concentration is observed. Probably the long-range effect is observed by positron annihilation method.